Isolation and characterization of new lignin streams derived from extractive-ammonia (EA) pretreatment - Sousa, Leonardo da Costa; Foston, Marcus; Bokade, Vijay V.; Azarpira, Ali; Lu, Fachuang; Ragauskas, Arthur J.; Ralph, John; Dale, Bruce E.; Balan, Venkatesh (Green Chemistry, 2016)
One of the key challenges facing lignin conversion to fuels and chemicals is related to the level of carbohydrate and ash impurities found in extracted lignin. Structural modifications of lignin may also occur as a result of biomass pretreatment and harsh lignin extraction protocols. Extractive-Ammonia (EA) is a new pretreatment technology that uses liquid ammonia to cleave lignin-carbohydrate complexes, decrystallize cellulose, solubilize lignin, and selectively extract Lignin from lignocellulosic biomass, enabling better utilization of both lignin and carbohydrate components in a biorefinery. The EA-based biorefinery produces two different lignin-rich streams, with different properties, that could potentially be upgraded to fuels and chemicals using green processes. In this work, a water/ethanol-based fractionation method was developed to enrich the ammonia-soluble extractives, resulting in a major product stream containing 92% lignin. Detailed characterization of the various streams resulting from EA treatment, including compositional analysis, structural characterization by nuclear magnetic resonance (NMR) spectrometry, elemental analysis, molecular weight analysis, and thermo-gravimetric analysis provides a broad evaluation of the EA derived lignin product stream structures and properties, assessing their potential for commercial applications. In summary, EA-derived lignins preserve much of lignin's functionality, including the sensitive (3-aryl ether units. Nitrogen incorporation was observed in the lignin-rich streams, notably due to the presence of hydroxycinnamoyl amides formed during ammonia pretreatment.